Produção e qualidade da silagem de milho em diferentes espaçamentos e populações de plantas - Penteado, Felipe Grisard (2023)
The objective was to evaluate different spacing between rows and plant populations on the production and quality of corn silage in Southwest Paraná. The experimental design was randomized blocks with treatments in a 2x3x4 factorial arrangement, two agricultural years (2019/2020 and 2020/2021), three row spacings (45 cm, 90 cm and rows with interspersed spacings of 45 and 90 cm) and four plant populations (50, 60, 70 and 80 thousand plants/ha). The hybrid B2688 PWU was implemented in plots measuring 6 x 6.3 meters, using four replications per year. Plant height, ear insertion, stem diameter, number of grains per row, number of rows per ear, thousand grain weight (PMG), stem proportion, leaf proportion, grain proportion, straw + cob proportion were evaluated, forage dry matter productivity, pH, crude protein (CP), neutral detergent fiber, potassium (K) and phosphorus (P) content of silage, as well as exports of N, P and K. The data were subjected to analysis of variance and the means were compared using the Tukey test (harvest and spacing). Regression analysis was used for the quantitative factor (plant population). The quantitative characteristics, except final plant stand, were influenced by the agricultural year, with worse results being observed for the second agricultural year. Plant height, ear insertion height and leaf proportion increased with increasing plant population. The stem diameter, number of grains per row, weight of a thousand grains and proportion of straw + cob were reduced with the increase in plant population. The number of rows per ear, the proportion of grains and stalks were not influenced by plant populations. Silage dry matter productivity peaked at 74.3 thousand plants/ha in the first agricultural year, while in the second agricultural year, forage productivity increased linearly due to the increase in plant population. Row spacing only influenced ear insertion height, number of grains per row, proportion of straw + cob and forage productivity. The ear insertion height was lower in the spacing with rows of 45 and 90 cm interspersed. The number of grains per row was lower in the row spacing of 45 cm compared to the row spacing of 90 cm, which did not differ from the spacing with interspersed rows of 45 and 90 cm. This spacing showed a higher proportion of straw + cob. Silage productivity was higher at 45 cm spacing. The pH, crude protein content and export of nitrogen, phosphorus and potassium were higher in the first agricultural year. The neutral detergent fiber content of the silage was higher in the second agricultural year. The plant population did not change the qualitative aspects of the silage, except pH, which increased linearly in the first agricultural year with the increase in plant population. Nitrogen export reached a maximum point of 72.4 thousand plants/ha, while phosphorus and potassium export increased linearly with the increase in plant population. An interaction between spacing and agricultural year was verified for pH, crude protein content and neutral detergent fiber in the silage. Spacing did not influence nitrogen export. Spacing with interspersed rows of 45 and 90 cm promoted greater export of phosphorus and potassium. In periods without stressful factors, such as drought and pest pressure, the silage productivity of the B2688 hybrid is maximized with approximately 74 thousand plants/ha, while in periods of water stress and leafhopper pressure, silage productivity increases between 50 and 80 thousand plants/ha. The row spacing of 45 cm allows for greater silage productivity.